2019
DOI: 10.1177/1756286419878324
|View full text |Cite
|
Sign up to set email alerts
|

Extended treatment with fingolimod for relapsing multiple sclerosis: the 14-year LONGTERMS study results

Abstract: Background: Multiple sclerosis (MS) is a chronic disease that may require decades of ongoing treatment. Therefore, the long-term safety and efficacy of disease-modifying therapies is an important consideration. Methods: The LONGTERMS study evaluated the safety and efficacy of fingolimod in patients with relapsing MS (RMS) with up to 14 years of exposure. This phase IIIb, open-label extension study included patients aged ⩾ 18 years with confirmed RMS diagnosis who completed previous phase II/III/IIIb core/exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 37 publications
7
44
1
1
Order By: Relevance
“…The present post hoc biomarker analysis included pooled data from patients with RRMS who were randomly assigned to receive fingolimod 0.5 mg once daily during the core period of the 24-month FTY720 Research Evaluating Effects of Daily Oral therapy in Multiple Sclerosis (FREEDOMS) (NCT00289978) 14 or 12-month Trial Assessing Injectable Interferon vs FTY720 Oral in Relapsing -Remitting Multiple Sclerosis (TRANSFORMS) (NCT00340834) 15 phase 3 trials (both trials had essentially the same inclusion/exclusion criteria), continued on the same treatment and dose in the respective extension studies (NCT00662649 and NCT00340834), 16 , 17 and thereafter transitioned into the open-label long-term extension LONGTERMS study for up to 10 years (NCT01201356). 18 Details of the individual study design and patient population are reported elsewhere. 14 18 NfL analysis was performed in all samples where informed consent was granted, irrespective of clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present post hoc biomarker analysis included pooled data from patients with RRMS who were randomly assigned to receive fingolimod 0.5 mg once daily during the core period of the 24-month FTY720 Research Evaluating Effects of Daily Oral therapy in Multiple Sclerosis (FREEDOMS) (NCT00289978) 14 or 12-month Trial Assessing Injectable Interferon vs FTY720 Oral in Relapsing -Remitting Multiple Sclerosis (TRANSFORMS) (NCT00340834) 15 phase 3 trials (both trials had essentially the same inclusion/exclusion criteria), continued on the same treatment and dose in the respective extension studies (NCT00662649 and NCT00340834), 16 , 17 and thereafter transitioned into the open-label long-term extension LONGTERMS study for up to 10 years (NCT01201356). 18 Details of the individual study design and patient population are reported elsewhere. 14 18 NfL analysis was performed in all samples where informed consent was granted, irrespective of clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…18 Details of the individual study design and patient population are reported elsewhere. [14][15][16][17][18] NfL analysis was performed in all samples where informed consent was granted, irrespective of clinical outcomes.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…Fingolimod (FTY720) is an immunosuppressant which prevents lymphocyte egress from the lymph nodes, thereby, reducing autoaggressive lymphocyte migration into the central nervous system. Fingolimod (FTY720) is currently used in the treatment of relapsing multiple sclerosis [121]. In addition, it is safe and well-tolerated and can reduce circulating lymphocytes in patients suffering from amyotrophic lateral sclerosis [122].…”
Section: S1pr In Nervous Systemmentioning
confidence: 99%
“…In addition, Bondì et al [128] observed that S1P/S1PR3 axis plays a negative role in muscle mass maintenance and force in soleus during aging and extracellular S1P exerts a protective effect during muscle fatigue development [129]. S1P/S1PR3 signaling also modulates excitation-contraction coupling and intracellular calcium mobilization [121][122][123][124][125][126][127][128][129][130].…”
Section: S1pr In Skeletal Muscle Systemmentioning
confidence: 99%
“…При более активном течении РС и недостаточной эффективности этих препаратов используются более сильные ЛС, однако они имеют и более широкий спектр побочных эффектов. Опыт применения этих препаратов также достаточно большой -более 10 лет [7].…”
Section: современные требования к исследованиям лекарственных средствunclassified